2006
DOI: 10.1103/physrevlett.97.156101
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-Up Assembly of Single-Domain Titania Nanosheets on(1×2)Pt(110)

Abstract: A bottom-up route towards the synthesis of titania nanosheets is explored, alternative to the exfoliation of layered titanates. Nanosheets are assembled from the constituent elements and epitaxially matched to a suitable substrate: (1 x 2)-Pt(110). Their basic lepidocrocite structure is modulated at the nanoscale due to coincidence with the substrate. Density functional calculations reveal the structure details of the nanosheet, which is also shown to be in close relationship with a (001)-oriented anatase bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 31 publications
4
58
0
4
Order By: Relevance
“…Die vielfältigen Anwendungen, die auf Festkörper/Gas-Grenzflächeneffekten beruhen, [1,47,48] erhöhen zudem den Bedarf an oberflächenchemischen Untersuchungen nanoskaliger Oxidschichten. [13,49] …”
Section: Zuschriftenunclassified
See 1 more Smart Citation
“…Die vielfältigen Anwendungen, die auf Festkörper/Gas-Grenzflächeneffekten beruhen, [1,47,48] erhöhen zudem den Bedarf an oberflächenchemischen Untersuchungen nanoskaliger Oxidschichten. [13,49] …”
Section: Zuschriftenunclassified
“…B. einer stark erhöhten Azididät, [10] oder von Oberflächenstrukturen, die bei den ausgedehnten und dreidimensionalen Festkörpern nicht auftreten. [11][12][13] Die Fortschritte bei der Synthese neuer Materialien in den letzten Jahren haben eine Klasse morphologisch definierter Nanostrukturen verfügbar gemacht, die sich vorzüglich als Modellsysteme zur Untersuchung chemischer und photochemischer Fragestellungen eignen. [14][15][16][17][18][19] Für die Herstellung von Na 2 Ti 3 O 7 -Nanodrähten (Abbildung 1 a) erhitzten wir kommerziell erhältliches TiO 2 -Pulver (Alfa-Aesar-Nr.…”
unclassified
“…[11] The same lepidocrocite-like structure with an almost identical unit cell has also been found in the early stages of epitaxy on (1 2)-Pt(110) under the same preparative conditions; however, in this case, the NS forms a 14 4 commensurate superstructure with respect to the substrate. [12,13] Herein we extend the previous work to a thicker nanolayer (NL) [hereafter referred to as rect'-TiO 2 ] obtained by longer reactive deposition of Ti in an O 2 background both on the Pt(111) and (1 2)-Pt(110) surfaces, and we discuss its structure and morphology in detail, on the basis of low-energy electron diffraction (LEED), scanning tunneling microscopy (STM) experimental data and theoretical density functional theory (DFT) simulations. Moreover, the observed experimental data have been directly compared with the predictions of theoretical calculations on the self-standing NLs.…”
Section: Introductionmentioning
confidence: 97%
“…[9,10] On the other hand, when a higher oxygen background is used, fully stoichiometric NSs of different thickness can be prepared, where oxygen atoms are located at the interface with the Pt substrate. [11][12][13] In particular, we have already shown that a lepidocrocitelike [14] fully stoichiometric NS (named rect-TiO 2 according to the previously reported nomenclature) can be formed under strongly oxidative conditions (P O2 = 1 10 À4 Pa) on both Pt (111) and (1 2)-Pt(110) surfaces: [11][12][13] On the former it has been found that the NS is characterized by a rectangular unit cell and that the film is incommensurate with respect to the substrate. [11] The same lepidocrocite-like structure with an almost identical unit cell has also been found in the early stages of epitaxy on (1 2)-Pt(110) under the same preparative conditions; however, in this case, the NS forms a 14 4 commensurate superstructure with respect to the substrate.…”
Section: Introductionmentioning
confidence: 98%
“…62 The interest in this technique is motivated by its simplicity and the use of inexpensive starting materials. Recently, alternative bottom-up methods have been proposed, both through vapor deposition 68 and in aqueous solution, [69][70][71] but high cost, low product crystallinity and poor reproducibility of the results still limit their widespread application.…”
Section: Titanium Oxide Nanosheets (Tixo2)mentioning
confidence: 99%